Inducible l-Alanine Exporter Encoded by the Novel Gene ygaW (alaE) in Escherichia coli - Hori, Hatsuhiro (American Society for Microbiology, 2011)

(untitled)
We previously isolated a mutant hypersensitive to l-alanyl-l-alanine from a non-l-alanine-metabolizing Escherichia coli strain and found that it lacked an inducible l-alanine export system. Consequently, this mutant showed a significant accumulation of intracellular l-alanine and a reduction in the l-alanine export rate compared to the parent strain. When the mutant was used as a host to clone a gene(s) that complements the dipeptide-hypersensitive phenotype, two uncharacterized genes, ygaW and ytfF, and two characterized genes, yddG and yeaS, were identified. Overexpression of each gene in the mutant resulted in a decrease in the intracellular l-alanine level and enhancement of the l-alanine export rate in the presence of the dipeptide, suggesting that their products function as exporters of l-alanine. Since ygaW exhibited the most striking impact on both the intra- and the extracellular l-alanine levels among the four genes identified, we disrupted the ygaW gene in the non-l-alanine-metabolizing strain. The resulting isogenic mutant showed the same intra- and extracellular l-alanine levels as observed in the dipeptide-hypersensitive mutant obtained by chemical mutagenesis. When each gene was overexpressed in the wild-type strain, which does not intrinsically excrete alanine, only the ygaW gene conferred on the cells the ability to excrete alanine. In addition, expression of the ygaW gene was induced in the presence of the dipeptide. On the basis of these results, we concluded that YgaW is likely to be the physiologically most relevant exporter for l-alanine in E. coli and proposed that the gene be redesignated alaE for alanine export.